Formation of plutonium(iv) silicate species in very alkaline reactive media. Issue 36 (19th August 2021) - Estevenon, Paul; Dumas, Thomas; Solari, Pier Lorenzo; Welcomme, Eleonore; Szenknect, Stephanie; Mesbah, Adel; Kvashnina, Kristina O.; Moisy, Philippe; Poinssot, Christophe; Dacheux, Nicolas
Abstract : Thanks to XAS, sequential filtration and α spectrometry, formation of Pu(iv ) silicate colloids of 6 nm in size was evidenced for pH > 13 and Pu concentration of 10 mM. These species could affect the plutonium mobility under environmental conditions. Abstract : Studying the speciation of Pu(iv ) in very alkaline and silicate ion rich reactive media allowed identification of the formation of plutonium(iv )-silicate colloidal suspensions which were stable for months. These colloids were stabilized in aqueous solution for pH > 13 and for concentrations around 10 −2 mol L −1 . Successive filtration processes allowed evaluation of their size, which was found to be smaller than 6 nm. Their structural characterization by XAS evidenced that their structure was similar to those identified for the other tetravalent actinide-silicate colloidal systems like thorium, uranium and neptunium. Their formation could explain the increase of plutonium solubility usually observed in alkaline silicate-rich solutions and could affect the plutonium mobility as a result in contaminated sites or in other environmental permeable media.